2012
DOI: 10.1002/app.36660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetization on the gel structure and protein electrophoresis in polyacrylamide hydrogel nanocomposites

Abstract: In this study, polyacrylamide nanocomposite hydrogels were formulated in combination with sodium montmorillonite (MMT) in the presence of a 2-T magnetic field. This top-down nanomanufacturing approach led to interesting changes in the internal structure of the gel and ultimately to a dramatic improvement in the ability of the composite to separate the two protein probes, ovum serum albumin and carbonic anhydrase. The morphology of the nanocomposite hydrogel was analyzed with cryogenic scanning and transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
(60 reference statements)
3
10
0
Order By: Relevance
“…In particular, and as an overall conclusion, this study suggests that the magnetic alignment of nanoparticles within the gels achieved by Thompson et al (2012) and that showed potential for improving separation has now a possibly fundamental explanation based on the study reported here. This study also suggests (for the first time and to the best of our knowledge) a possible useful approach to choose both a favorable hydrogel morphology as well as optimal values of the operating parameters for a given type of separation medium The use of nanoparticles (Thompson et al, 2010;Thompson et al, 2012) such as ceramic, metallic or polymer types might be an excellent way to achieve this objective by orienting them during the gels manufacture with the use of magnetic fields, for example.…”
Section: Summary and Concluding Remarkssupporting
confidence: 74%
See 2 more Smart Citations
“…In particular, and as an overall conclusion, this study suggests that the magnetic alignment of nanoparticles within the gels achieved by Thompson et al (2012) and that showed potential for improving separation has now a possibly fundamental explanation based on the study reported here. This study also suggests (for the first time and to the best of our knowledge) a possible useful approach to choose both a favorable hydrogel morphology as well as optimal values of the operating parameters for a given type of separation medium The use of nanoparticles (Thompson et al, 2010;Thompson et al, 2012) such as ceramic, metallic or polymer types might be an excellent way to achieve this objective by orienting them during the gels manufacture with the use of magnetic fields, for example.…”
Section: Summary and Concluding Remarkssupporting
confidence: 74%
“…Therefore, a systematic optimization-based approach is appealing because an optimal separation of practical use can be achieved efficiently from a complete understanding of all possibilities. This (overall) morphology-based optimization could be helpful in assisting potential new designs that work towards systematically generating a multidimensional structure having broader tunability (Thompson et al, 2008) for a given type of molecule.…”
Section: Optimization Methodologies In Designing New Morphological Stmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 However, these techniques measure the total magnetic response of the probed region of the sample, and a large dia-or paramagnetic response can make the detection of a small superparamagnetic contribution difficult and time-consuming. Nanocomposites, composite materials where at least one constituent has a size on the order of nanometers, have become important materials with many current and future applications, 22 such as in batteries, 23 antibacterial materials, 24 biochemistry, 25 magnetic-field controlled electrical devices, 26 and many others. Nanocomposite material properties not only depend on the properties of their constituent materials but also strongly depend on their morphology, dispersion, and interfacial characteristics of the constituents.…”
mentioning
confidence: 99%
“…Nanocomposite material properties not only depend on the properties of their constituent materials but also strongly depend on their morphology, dispersion, and interfacial characteristics of the constituents. [22][23][24][25][26][27] The increase in research on nanoscale materials has been driven by the ability to characterize these materials. 28 In order to further advance the field, new characterization techniques are necessary that are accessible to many researchers.…”
mentioning
confidence: 99%